The Correlation Between Family Environment and Mathematics Learning Outcomes of Tenth-Grade High School Students’ - Fathia Aiva Maharani; Dealova Syarmilano; Annisa Putri Suryanti; Novita Sari; Rahma Siska Utari; Yovika Sukma; Muhammad Ridho (Universitas Mercu Buana Yogyakarta, 2026)
This study investigates the relationship between family environment and mathematics achievement of 10th-grade students at a high school in Teluk Gelam, Ogan Komering Ilir. A quantitative approach with a correlational design was employed, with 30 students selected as the total sample using cluster random sampling technique. Data collection was conducted using two instruments: a family environment questionnaire with a Likert scale consisting of 14 closed-ended items, and documentation of mid-semester exam scores as an indicator of student learning outcomes. The questionnaire’s validity was tested using the Corrected Item-Total Correlation method, and its reliability was assessed using Cronbach’s Alpha, yielding a value of 0.823. Data analysis was performed using Spearman’s Rank Correlation test based on the results of the Shapiro-Wilk normality test, which indicated that one of the variables was not normally distributed. The results of the study showed a Spearman correlation coefficient of 0.002 with a significance value of 0.990. These results indicate that there is no significant relationship between the family environment and students’ mathematics learning outcomes. This suggests that students’ mathematics learning outcomes are likely more influenced by a combination of other factors, such as learning motivation, prior ability, the quality of instruction, and the school environment.